AKTIVITAS ANTIVIRAL JAMU VIRANUR (Piper cubeba, Foeniculum vulgae mill, Curcuma heyneana) 1% TERHADAP VIRUS Avian Influenza - , YUDHYA SEKAR LOLITA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Avian Influenza is one of the zoonosis disease on poultry which has high mortality. Antiviral drugs always raise resistant effect, alternative medicine should be invented by the next invention. Viranur as herbal medicine had ability to decrease the growth of Dengue virus. This research aimed fo find the effect of viranur on Avian Influenza virus based on haemaglutination assay (HA). This research used 13 embryonic chiken eggs which devided in to 5 groups and inoculated with virus each group, exception of group 5. Group 1 as control which did not inoculate with virus. Group 2 was inoculated with viranur 2%. Group 3 was inoculated with viranur 1%. Group 4 was inoculated with viranur 0,5%. Group 5 whitch was inoculated with viranur 2% without virus. All of eggs were incubated on 37Â°C for three days. Incubated eggs restored on refrigerator for 18 hours. Harvesting of allantoic fluid was done to measure viral titer by HA test. Result of research analized and compared with T-test and one way ANOVA. Based on statictics measurement group 1, group 2 and group 3 had significant difference (p<0,05). Group 1 and group 4 had no significant difference (p>0,05). Conclusion of research was that viranur 1% and 2% could decrease HA titer significantly and had antiviral activity 100%.